Cover Image, Volume 37, Issue 10. Issue 10 (13th September 2016) - Thomas, Anne; Biswas, Arijit; Dodt, Johannes; Philippou, Helen; Hethershaw, Emma; Ensikat, Hans Juergen; Ivaskevicius, Vytautas; Oldenburg, Johannes
Abstract : On the cover : The cover image, by Arijit Biswas et al., is based on the Research Article Coagulation Factor XIIIA Subunit Missense Mutations Affect Structure and Function at the Various Steps of Factor XIII Action, Pages 1030–1041, DOI:10.1002/humu.23041 .